Analisis Paragraf Kategori Leksikal–Struktural Pada Teks Pidato Menteri Pemuda dan Olahraga Pada Hari Sumpah Pemuda Ke-97 Tahun 2025 - Kareyau, Gibson Lenny; Amanda, Maulana Wira; Sari, Novi Faulia; Kurniawan, Eva Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The speech delivered by the Minister of Youth and Sports on the 97th Anniversary of Youth Pledge Day in 2025 represents a formal state discourse conveying messages of unity, nationalism, and the strategic role of youth in nation-building. This study aims to analyze the use of lexical and structural categories in the speech text and to explain their functions in constructing discourse cohesion and persuasive power. The research employs a qualitative descriptive method with a linguistic analysis approach using observation and note-taking techniques. The data consist of linguistic elements in the speech text, which are classified into lexical and structural categories and analyzed based on their functions and frequency of occurrence. The findings indicate that lexical elements are more dominant than structural elements, accounting for approximately 70–75% of the total data, while structural elements comprise around 25–30%. The dominance of lexical elements, particularly nouns, verbs, and adjectives, functions as the main carriers of meaning that emphasize national identity, unity, and collective appeals. It can be concluded that high lexical density serves as an effective linguistic strategy in strengthening the persuasive message of the state speech.